2023
DOI: 10.1098/rspb.2022.2293
|View full text |Cite
|
Sign up to set email alerts
|

Macroevolution of protective coloration across caterpillars reflects relationships with host plants

Abstract: A critical function of animal coloration is avoiding attack, either by warning predators or reducing detectability. Evolution of these divergent strategies may depend on prey palatability and apparency to predators: conspicuous coloration may be favoured if species are distasteful, or habitats make hiding difficult; by contrast, camouflage may be effective if prey lack defences or environments are visually complex. For insect herbivores, host plants provide both chemical defence and the background against whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 109 publications
2
9
1
Order By: Relevance
“…Previous work has found that bands may be linked to sociality across various taxa [43] yet, despite the potential enhancement of the warning signal by grouping overall [13,37,41,42], we found no evidence that specific aposematic patterns are used more by solitary or gregarious larvae. This is aligned with previous findings that the patterns of warning signals are of secondary importance to avian predators, which instead focus primarily on colour [10][11][12].…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…Previous work has found that bands may be linked to sociality across various taxa [43] yet, despite the potential enhancement of the warning signal by grouping overall [13,37,41,42], we found no evidence that specific aposematic patterns are used more by solitary or gregarious larvae. This is aligned with previous findings that the patterns of warning signals are of secondary importance to avian predators, which instead focus primarily on colour [10][11][12].…”
Section: Discussioncontrasting
confidence: 96%
“…For aposematic species, our findings support those of a recent study using a similar approach [13], in that larvae are most likely to use a pattern of colour-contrasting, horizontal bands or spots. This suggests there is some inherent quality (or qualities) of these patterns which support effective aposematic signalling.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations